Evaluation of Android-Based Mobile Application for Student Grade Management at SMKN 1 Payakumbuh - Tridiana, Rince (Jurnal Vokasi Teknik Informatika, 2025)
Teachers play an essential role in conducting learning assessments; however, manual grade recording remains a challenge due to high administrative workloads and time constraints. These limitations often lead to inaccuracies and delays in academic data processing. Therefore, this study aimed to evaluate the practicality and effectiveness of an Android-based grade management application designed to support teachers in administering student assessments more efficiently. The research was conducted at SMK Negeri 1 Payakumbuh involving two practitioners and twenty subject teachers as respondents. Practicality data were collected through a questionnaire consisting of three assessed aspects: ease of use, flexibility, and features and functionality. The results showed that the application achieved an average practicality score of 89.17% based on practitioners’ responses and 84.50% based on subject teachers’ responses, both of which fall into the “very practical” category. These findings indicate that the application is easy to operate, accessible, and supportive of mobile-based administrative tasks. Furthermore, effectiveness was tested by comparing post-test results between a control group (manual grade entry) and an experimental group (using the application). Statistical analysis using an independent samples t-test demonstrated a significant difference in performance (p = 0.000 < 0.05), with the experimental group achieving a higher average score of 77.8 compared to 65.5 in the control group. This confirms that the Android-based application improves accuracy and efficiency in grade processing. In conclusion, the developed grade management application is both practical and effective, and it has strong potential to assist teachers in simplifying assessment administration through a fast, accurate.